BEING ACTIVE READERS BY APPLYING CRITICAL READING TECHNIQUE - NINA SUZANNE (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
Critical reading is a reading technique that encourages the students to have deeper comprehension on the materials they are reading. Analyzing and evaluating the reading materials by proposing several critical questions to the writer, known as ‘reading between the lines”, can direct the reading to ‘advance’ level. Consequently, the students do not just take for granted what they are reading. However, to become a critical reader is not easy since there are some potential obstacles that the reader might encounter. Consequently, they have to be able to deal with the obstacles and therefore become critical and active readers.Key words: critical reading, critical readers, critical thinking, and active readers